Dynamic characteristics analysis of WEDM based on Ansys and LMS - Jingxing Qi; Changtao Cai; Zhixing Mao; Dongdong Luo (Institute of Advanced Engineering and Science, 2014)
In the operation process,the Wire Electrical Discharge Machine(WEDM) has certain imperfections such as vibration and the descent of machine precision which vibration produces.This paper studies the dynamic parameter of the machine tool and optimizes the natural frequency and vibration.Taking the DK7725 taper machine tool as an example,the paper establishes a 3Dmodel with ProEngineer 5.0.According to the Masataks Yoshimura method,the authors could ascertain the stiffness and damping of joint surfaces among machine main parts and ascertain the equivalent dynamic model. In order to have a modal analysis about the machine tool structure,the virtual dynamic analysis module of ANSYS Workbench Environment(AWE) is used.Through the study of dynamic parameter,the authors optimize and improve the natural frequency and vibration of machine tools, compared with the finite element analysis results and the no-optimization data.And the final results show that the change rates of each order natural frequencies optimized ranges from 0%to18.9%,and the whole mechine’s optimization achieves satisfied effect.